Heterogeneity in the Prevalence of High-Risk Human Papillomavirus Infection in Human Immunodeficiency Virus-Negative and Human Immunodeficiency Virus-Positive Men Who Have Sex With Men in West Africa - (:unkn) unknown (My University, 2021)
Background: Men who have sex with men (MSM) are at high risk of human papillomavirus (HPV) infection. We assessed (i) the prevalence of high-risk HPV (HR-HPV) infection and associated factors, and (ii) the prevalence of vaccine-preventable HPV infections in MSM in Burkina Faso, Côte d'Ivoire, Mali, and Togo.Methods: A cross-sectional study was conducted in 2017-2018 among MSM ≥18 years old followed in community-based clinics. HPV infection was investigated in oral and anal samples using the e-BRID system. Factors associated with HR-HPV infection were identified using multivariate logistic regressions.Results: Among 631 participants, 425 were HIV-negative and 206 HIV-positive. HR-HPV prevalence ranged from 9.2% to 34.8% in the former, and 33.3% to 71.0% in the latter, according to the study country. In multivariate analysis, HIV infection (adjusted odds ratio (aOR) 3.61, 95% confidence interval (CI) 2.48-5.27) and study country (4.73, 2.66-8.43 for Mali; 3.12, 1.68-5.80 for Burkina Faso; 3.51, 1.92-6.42 for Togo) were associated with HR-HPV infection. Other associated factors were low educational level, self-defined homosexual identity, and condomless anal sex. The prevalence of infections which can be prevented with bivalent, quadrivalent, and nonavalent vaccines was 5.9, 27.1, and 34.6% in HIV-negative participants, and 18.9, 43.7, and 54.9% in HIV-positive participants, respectively.Conclusions: HR-HPV prevalence was very heterogeneous between the study countries in both HIV-negative and HIV-positive MSM. Vaccine-preventable HPV infections predominated. Vaccination should be proposed to young MSM to reduce the burden of HPV infection in this vulnerable population and their female partners in West Africa.
Keywords: African Research